(3GdbhGYO GdEdgjIs - (3GdHMQGfj, ceGd GdOjf, ejKe Hf Ydj Hf ejKe, J (B681 (3g`s ((3OGQ GdSdWfI HJHQjRs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3adeG cGf TQa GdYde HTQa GdeYdhe hcdeG cGf GdeYdhe CLd hCYdi cGf GdYde Hg HGdQYGjI Chdi hcGfJ PGJ GdHGQj SHMGfg CTQa GdeYdheGJ (B...s
(3BNQgG (B:s
... (3hEPG LGR Pdc aj GdWQajf ade dG jG jLhR eKdg aj GdhGSWI CYfj WHbI GdChdjGA hHGddg GdJhajb hGdYUeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGdCYdGe , ddRQcdj (B7\336s
(3GdPQjYI (B17 - 117 (940)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds